2018
DOI: 10.7554/elife.39234
|View full text |Cite
|
Sign up to set email alerts
|

Transition between fermentation and respiration determines history-dependent behavior in fluctuating carbon sources

Abstract: Cells constantly adapt to environmental fluctuations. These physiological changes require time and therefore cause a lag phase during which the cells do not function optimally. Interestingly, past exposure to an environmental condition can shorten the time needed to adapt when the condition re-occurs, even in daughter cells that never directly encountered the initial condition. Here, we use the molecular toolbox of Saccharomyces cerevisiae to systematically unravel the molecular mechanism underlying such histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 74 publications
5
72
0
Order By: Relevance
“…For instance, a study of S. cerevisiae cells from a glucose-containing (sole carbon source) medium were placed into a maltose-containing medium revealed profound differences in lag phase times. Indeed, up to 90% of cells never left the lag phase during the experimental period 101 , which may indicate genetic and/or epigenetic variation within the population; either of which can provide the basis for evolutionary changes 99 . Further examples can be found in the recent review by Bertrand 86 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study of S. cerevisiae cells from a glucose-containing (sole carbon source) medium were placed into a maltose-containing medium revealed profound differences in lag phase times. Indeed, up to 90% of cells never left the lag phase during the experimental period 101 , which may indicate genetic and/or epigenetic variation within the population; either of which can provide the basis for evolutionary changes 99 . Further examples can be found in the recent review by Bertrand 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that genetically identical cells can vary in the time they need to adapt to the same nutrient switch (lag time), and often a fraction of cells cannot adapt at all [2][3][4][5][6][7][8][9]. This heterogeneity in response is primarily due to phenotypic differences among cells at the time of the switch, for instance in their protein levels or metabolic fluxes [2][3][4][5][6][7][8][9][10]. For example, the ability of Escherichia coli cells to switch from growth on glucose to growth on lactose depends on how many proteins of the lactose pathway the cells have at the time of the switch [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that this lag phase is a result of maintenance and propagation in media containing glucose as the only carbon source. The lag phase duration during a glucoseto-maltose shift in S. cerevisiae appears to be dependent mainly on the repressive effects of glucose on the respiratory metabolism [45]. With S. paradoxus, glucose repression seems to play a strong and a crucial role in the ability of the strains to use maltose.…”
Section: Discussionmentioning
confidence: 99%